Estudo de caso da aplicação do método de análise de modo e efeito de falha potencial na indústria automotiva - Lima, Reinaldo Vaz de (2022)
National automotive industry corresponds to approximately 20% of transformation industries GDP and, with the customer growing exigence, this sector faces the demand of always increase quality, but with few implements in costs. Allied with the low success of project development, companies look for a way to improve the financial results of products and processes, focusing on risk reduction and the increase of reliability. In this context, one of the risk investigation methods that stands out is FMEA analysis, in which potential failure prediction and preventing happen before its occurrence, focused on issues preventing, highlighting the security, and adding customer satisfaction. This tool is widely used in several industrial branches and many times in products life cycle. Thus, the following work is about a design DFMEA Analysis development applied on an automotive fueling system, in which one of the objectives is to find probable causes of potential failure modes, generating action plans to mitigate its occurrence and, if the risk mode does occur, its effects. This work was developed applying SAE J1739 standard and several FMEA studies and applications, including works aimed at the automotive and fueling environment. Finally, some system improvements are suggested, which could be applied to improve the component’s reliability in sense that they are not susceptible to the probable failure modes identified with the highest number of severity, occurrence, detectability and, consequently, the highest selected risk priority numbers. From that an action plan is generated an applied, which the objective to mitigate risks and failures. Finally, the FMEA is redone, finding the new RPN values to the, previously, mainly items.